Halocins and lanthipeptides from Haloferax mediterranei - Castro, Inês Manuel de Sousa Martins de (2022)
The study of archaea's secondary metabolites, including archaeocins, is still limited. These antimicrobial peptides are poorly studied, especially when compared to the numerous studies on antibiotic production by other microorganisms. Only two types of archaeocins are known: i) halocins, produced by halophilic archaea and ii) sulfolobicins, produced by the extremely thermophilic Sulfolobus spp. There are also promising reports of archaeocins endowed with anticancer properties. Halophilic archaea have recently been found to be present in the human gut, thus showing that they are not confined to high salt environments alone. Halocins were firstly discovered in the 80’s and most of their characterization was solely based on supernatant-based assays. In fact, only a few halocins were successfully purified and sequenced, and even fewer have a proposed biosynthetic mechanism. Also, their mode of action, ecological role and biotechnological potential are still little explored. H. mediterranei ATCC 33500 has antiarchaeal activity. Studies determined that these strains produced the HalH4 halocin. However, over the last years, it was shown that strains lacking the halH4 gene retained their antiarchaeal ability. So, the molecule(s) responsible for its microbial activity is still unknown. This strain encodes in its genome three class II lanthipeptide synthetases (MedM1, MedM2 and MedM3) and some putative lanthipeptide precursor peptides. A high percentage of the lanthipeptides produced by Bacteria has antimicrobial activity. This study aimed to summarize the information available so far on haloarcheocins (the halocins produced by Archaea) at two levels: bibliographical and by analysing the gene clusters known so far using comparative genomics. For the haloarcheocin, HalC8, it was possible to determine the putative biosynthetic clusters involved in the production of HalC8 and HalC8-related peptides by Haloarchaea, which includes a protein of unknown function (HalU), two membrane-located peptides (HalP1 and HalP2) and a transcriptional regulator (HalR). Other aim of this study was to determine if the lanthipeptides of H. mediterranei ATCC 33500 were haloarcheocins contributing to its antimicrobial profile. To achieve this, knock-out mutants without medM1, medM2 and medM3 genes were obtained by employing the pop-in and pop-out strategy. It was found that approximately 20 days and 6 months are required to obtain a single or a triple knock-out strains, respectively. The bioactivity of the triple knock-out (ΔM1M2M3) was tested against other halobacteria. However, no differences were observed in the halos produced by the ΔM1M2M3 strain and its parental strain (WR510). These results prove that the putative class II lanthipeptides of H. mediterranei are not involved in its antiarchaeal profile. Thus, their function in haloarchaea is still to be unravelled.